2019
DOI: 10.14295/transportes.v27i3.2042
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of the VISSIM truck performance model using GPS data

Abstract: Simuladores de tráfego permitem avaliar cenários de maneira segura e com baixo custo. Todavia, os modelos matemáticos que os regem são ajustados para cenários frequentes no país de origem do simulador. No VISSIM, os modelos referentes ao deslocamento de caminhões simulam veículos com melhor desempenho, se comparados aos caminhões brasileiros. Este trabalho apresenta a calibração das funções de aceleração para caminhões do VISSIM, utilizando a diferença entre perfis de velocidade simulados e reais como medidas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The synthetic data were obtained from simulations carried out in Vissim 2020, which is able to simulate AVs (Sukennik, 2018), where behavioural and vehicle performance parameters of automobiles and HGV were recalibrated to better represent the traf ic on Brazilian freeways (Bethônico et al, 2016;Carvalho and Setti, 2019). The following sections present the research steps.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic data were obtained from simulations carried out in Vissim 2020, which is able to simulate AVs (Sukennik, 2018), where behavioural and vehicle performance parameters of automobiles and HGV were recalibrated to better represent the traf ic on Brazilian freeways (Bethônico et al, 2016;Carvalho and Setti, 2019). The following sections present the research steps.…”
Section: Methodsmentioning
confidence: 99%
“…The distribution obtained indicates that the studied stream has vehicles that are slower than those in the distribution adopted as default by Vissim. The recalibrated parameters for HGV performance were obtained from a previous study (Carvalho and Setti, 2019) and include: maximum and desired acceleration functions, cumulative weight and power functions, and dimensions. These parameters were input into the software for four categories of HGV that characterise leets of HGV that travel on freeways in São Paulo state (Carvalho and Setti, 2019).…”
Section: Simula On Modelmentioning
confidence: 99%
“…In this study, PTV Vissim Version 11 [32] was selected for the simulation platform: (1) because of its ability to render very realistic traffic animations from driver's field-of-view perspective, both forward and rearward looking; and (2) because of the authors' familiarity with the tool. Any other traffic microsimulation software with similar capabilities can also be used, provided that it has been previously calibrated to represent driving behaviour and heavy vehicle performance in a sufficiently realistic way [33,34].…”
Section: Microsimulation Approachmentioning
confidence: 99%
“…In this study, PTV Vissim Version 11 [60] was selected for the simulation platform: 1) because of its ability to render very realistic trac animations from driver's eld-of-view perspective, both forward and rearward looking; and 2) because of the student's familiarity with the tool. Any other trac microsimulation software with similar capabilities can also be used, provided that it has been previously calibrated to represent driving behavior and heavy vehicle performance in a suciently realistic way [13,61].…”
Section: Microsimulation Approachmentioning
confidence: 99%
“…These "local" highway capacity manuals represent drivers, infrastructure, and vehicles more precisely. Previous research has shown the need to adapt the HCM procedures to Brazilian conditions due to the inaccuracy of parameters, vehicle conditions, and highway infrastructure [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%